Upaya Mahasiswa Pendidikan Bahasa Arab Stambuk 2020 UIN Sumatera Utara Dalam Meningkatkan SDM & Spiritualitas di Desa Tanjung Putus, Kabupaten Langkat - Nst, Ana Hijrah; Nasution, Muhammad Rizky; Taufiq, Muhammad (Yayasan Daarul Huda Kruengmane, 2024)
This study aims to identify efforts made by Arabic language education students in 2020 in improving Human Resources (HR) and spirituality in Fidesa Tanjung Putus, Padang Tualang District, Langkat Regency. The community service research method with R&D (Research and Development) is an approach that combines scientific research activities and technological development with the aim of making a direct contribution to society. The results showed that Arabic language education students in 2020 had made various efforts to improve human resources and spirituality in Fidesa Tanjung Putus, such as holding training and workshops, organizing social and religious activities, and providing motivation and support to the local community. It is hoped that the results of this study can make a positive contribution to the development of education and spirituality in the region.